2023
DOI: 10.3390/toxins15040289
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Harmful Algal Bloom Toxin Microcystin and Increased Vibrio Occurrence as Climate-Change-Induced Biological Co-Stressors: Exposure and Disease Outcomes via Their Interaction with Gut–Liver–Brain Axis

Abstract: The effects of global warming are not limited to rising global temperatures and have set in motion a complex chain of events contributing to climate change. A consequence of global warming and the resultant climate change is the rise in cyanobacterial harmful algal blooms (cyano-HABs) across the world, which pose a threat to public health, aquatic biodiversity, and the livelihood of communities that depend on these water systems, such as farmers and fishers. An increase in cyano-HABs and their intensity is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 209 publications
0
5
0
Order By: Relevance
“…It plays a role in various disease conditions involving endocrine, humoral, metabolic, and immune pathways 69 . The impact of climate change on neurological diseases and gastrointestinal health, including the liver-brain axis, has been highlighted, with potential implications for metabolic liver diseases and associated neuropathologies 70 . The increased activity in chemokine signaling, Th1 and Th2 signaling, neuroinflammation signaling, synaptic long-term depression signaling, adipokine signaling, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a role in various disease conditions involving endocrine, humoral, metabolic, and immune pathways 69 . The impact of climate change on neurological diseases and gastrointestinal health, including the liver-brain axis, has been highlighted, with potential implications for metabolic liver diseases and associated neuropathologies 70 . The increased activity in chemokine signaling, Th1 and Th2 signaling, neuroinflammation signaling, synaptic long-term depression signaling, adipokine signaling, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The cyanobacteria-gut-brain axis represents an intriguing and relatively unexplored connection between the microbial world and the intricate communication network within the human body. While the specific mechanisms of interaction remain a subject of ongoing investigation ( 77 ), it is hypothesized that cyanobacteria may produce many different compounds or metabolites that can modulate neuronal activity. Understanding the cyanobacteria-gut-brain axis at the neuronal level opens new scenarios for research and unravelling the intricacies of this relationship may provide insights into the development of innovative therapies targeting the gut microbiome to positively influence brain function.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study showed that increased pathogenic Vibrio sp. occurs when algal toxins increase [72].…”
Section: Environmental Epidemiology and Ecotoxicitymentioning
confidence: 99%